Análise comparativa do impacto das variáveis atitudinais e do comportamento do consumidor nas vendas físicas de uma loja Pet Shop - Sakai, Maryanne Akemi (2018)
Companies have a wide range of information from their customers, such as their registration and last purchase data. For a service provider in a market like Pet Shops, know your customer and know what the variables are. which most impact on your purchases is of paramount importance. The study gain additional gains when improving the purchasing model through variables consumer attitudes. The RFM analysis (frequency, frequency and monetary value) contributed clients to be grouped according to frequency, frequency and value transaction. The methodology was complemented with semi-structured interviews, 140 respondents, and multivariate linear regression models. The object of the study was the Pet Shop located in São Paulo. Five regression models were used to verify the incremental gains with the incorporation of attitudinal variables. The model that obtained R2 (68.13%) was the one that considered as a response variable the mean value of transaction of the year 2017 and as explanatory variables the quintiles of recency, frequency, of value, in addition to incomplete higher education, pet be considered as a child or as a member family, amount of other pets and cluster of clients that need to be remembered. As As a result of the research, it is noted that the perception of the family vis-a-vis the pet prevailing in the decision to purchase services and products, making variables such as distance from the residence to the Pet Shop or household income become secondary when determining the attitudinal variables that most influence the purchase decision. Understand each client and how it relates to the pet allows you to increase your transaction value because the client seeks above all the welfare of your pet.